Using qualitative process evaluation in the development of a complex intervention to advance person-centred practice by pharmacists: The Medicines and Alcohol Consultation (MAC) - Mary Madden; Stephanie Morris; Duncan Stewart; Karl Atkin; Brendan Gough; Thomas Mills; Jim McCambridge (Elsevier, 2021)
In order to effectively evaluate complex interventions, there have been calls for the further integration of qualitative methods. Qualitative process studies of brief alcohol interventions and medicines reviews are notably lacking. This article provides a grounded example through the presentation of findings from an embedded qualitative process evaluation of a multi-site, pilot cluster RCT of a new intervention: the Medicines and Alcohol Consultation (MAC). MAC is designed to increase the capacity of community pharmacists (CPs) to conduct person-centred medicines reviews in which the subject of alcohol consumption is raised in connection with medications and associated health conditions. Participant-focused qualitative studies (interviews, observations, recorded consultations) sought to understand how CPs engaged with and implemented MAC in context. This article documents effects of the intervention on developing person-centred consultation practice and highlights how qualitative process studies can be used formatively to develop middle range programme theory and to optimise intervention design for testing in a definitive RCT.